2019
DOI: 10.1002/jnr.24393
|View full text |Cite
|
Sign up to set email alerts
|

Differential impacts on multiple forms of spatial and contextual memory in diazepam binding inhibitor knockout mice

Abstract: Learning and memory are fundamental processes that are disrupted in many neurological disorders including Alzheimer’s disease and epilepsy. The hippocampus plays an integral role in these functions, and modulation of synaptic transmission mediated by γ-aminobutyric acid (GABA) type-A receptors (GABAARs) impacts hippocampus-dependent learning and memory. The protein diazepam binding inhibitor (DBI) differentially modulates GABAARs in various brain regions, including hippocampus, and changes in DBI levels may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…More generally, it is important to mention that ACBP is expressed in several brain regions (e.g., amygdala, hippocampus) that are not commonly associated with the control of energy balance. Although the role of ACBP in these regions is still unclear, studies suggest that endogenous ACBP may play a role in social (56) and learning behavior (57). Importantly, we recently reported that astroglial ACBP deficiency does not affect anxiety in mice (31), ruling out the possibility that susceptibility to diet-induced obesity in ACBP GFAP KO mice is confounded by changes in anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 91%
“…More generally, it is important to mention that ACBP is expressed in several brain regions (e.g., amygdala, hippocampus) that are not commonly associated with the control of energy balance. Although the role of ACBP in these regions is still unclear, studies suggest that endogenous ACBP may play a role in social (56) and learning behavior (57). Importantly, we recently reported that astroglial ACBP deficiency does not affect anxiety in mice (31), ruling out the possibility that susceptibility to diet-induced obesity in ACBP GFAP KO mice is confounded by changes in anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 91%
“…What is more, we suggest GABA A R signaling in astrocytes could also be inhibited by downregulation of DBI. DBI selectively knockout mice has shown certain forms of impaired spatial learning and memory [ 62 ]. NMDARs express in a low abundance on astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…To first determine the associative learning and memory, we conducted the contextual fear conditioning test (Fig 2A). During the training day, mice were placed in a training context and received brief aversive stimuli (footshock, 2×, 0.5 mA, 2 s duration, 30 s interval; Clark et al , 2008; Ujjainwala et al , 2019). On the test day (24 h after the training), mice were re‐exposed to the training context and assessed for fear memory by measuring freezing behavior in the absence of footshock stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…We then employed the Barnes maze to determine whether the loss of Nedd4‐2 impacts spatial reference memory (Fig 2B, left; Ujjainwala et al , 2019). The mice were first trained to escape a brightly lighted circular field by finding a dark escape hole.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation